2010
DOI: 10.1111/j.1365-3040.2010.02167.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotic stress globally downregulates photosynthesis genes

Abstract: To determine if damage to foliage by biotic agents, including arthropods, fungi, bacteria and viral pathogens, universally downregulates the expression of genes involved in photosynthesis, we compared transcriptome data from microarray experiments after twenty two different forms of biotic damage on eight different plant species. Transcript levels of photosynthesis light reaction, carbon reduction cycle and pigment synthesis genes decreased regardless of the type of biotic attack. The corresponding upregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
332
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 491 publications
(404 citation statements)
references
References 140 publications
48
332
3
3
Order By: Relevance
“…The largest functional group corresponds to proteins involved in stress responses, mainly biotic stress, suggesting that RPL10B could have a role in the response to pathogens, and these responses may be common for UV-B responses. Diverse responses to UV-B radiation are shared with other stress responses, for example, against pathogens (Bilgin et al, 2010;Mukherjee et al, 2010;Fraire-VelĂĄzquez et al, 2011). Many proteins identified in the rpl10B mutant were also identified in Arabidopsis by proteome analysis after infection with Alternaria brassicicola (Mukherjee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The largest functional group corresponds to proteins involved in stress responses, mainly biotic stress, suggesting that RPL10B could have a role in the response to pathogens, and these responses may be common for UV-B responses. Diverse responses to UV-B radiation are shared with other stress responses, for example, against pathogens (Bilgin et al, 2010;Mukherjee et al, 2010;Fraire-VelĂĄzquez et al, 2011). Many proteins identified in the rpl10B mutant were also identified in Arabidopsis by proteome analysis after infection with Alternaria brassicicola (Mukherjee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the latter hypothesis, reduced photosynthesis in response to herbivory, is supported by actual measurements of changes in photosynthesis rate, photosynthesis-related gene expression, or production of proteins that are part of the photosynthetic apparatus (Reymond et al, 2004;Giri et al, 2006;Wei et al, 2009;Bilgin et al, 2010;Coppola et al, 2013;Appel et al, 2014). Reduced photosynthetic capacity can exceed what would be expected from the observed amount of foliar tissue that is removed (Zangerl et al, 2002).…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…The genes annotated with this term in these clusters encode many components of photosystems I and II. The concerted downregulation of photosynthesis during biotic stress is a well-known phenomenon and has been seen in many very different plant biotic interactions (Bilgin et al, 2010). It has been suggested that the downregulation of photosynthetic gene expression enables the plant's nitrogen resources to be reallocated for synthesis of new defense proteins.…”
Section: Metabolismmentioning
confidence: 99%